Dampak Korona pada SUTET 500 kV Terhadap Radio Interference - Christine Widyastuti; I Nyoman Bagus Yudha Dharma (Sekolah Tinggi Teknik PLN, 2019)
Corona can occur in SUTET because SUTET carries a high enough electric current and voltage, this causes excessive electrical pressure that is not proportional to the breakdown strength of the air around the conductor so that there will be a phenomenon where the electric field will collide with free electrons in the air and will form ionisations in the form of new ions and electrons. This process will continue as long as there are currents and voltages on the extra-high-voltage network. This certainly will affect the surrounding environment through which SUTET is included, among others, interference with radio waves (Radio Interference). The addition of the number of sub conductors is considered more effective in reducing corona losses and radio interference in each wicket than increasing the distance of the conductor to the ground. The impact of corona on a 500 kV double-channel SUTET on radio interference in the Greater Jakarta area is still within reasonable limits because it is still below the IEEE standard of 40 dB.